2021
DOI: 10.1021/acs.jafc.1c01388
|View full text |Cite
|
Sign up to set email alerts
|

Combination of α-Glycosyl-Isoquercitrin and Soybean Fiber Promotes Quercetin Bioavailability and Glucagon-like Peptide-1 Secretion and Improves Glucose Homeostasis in Rats Fed a High-Fat High-Sucrose Diet

Abstract: This study examined the effects of a combination of soybean fiber and α-glycosyl-isoquercitrin (AGIQ) on improving quercetin bioavailability and glucose metabolism in rats fed an obesogenic diet. For 9 weeks, rats were individually fed a control diet, a high-fat high-sucrose (H) diet, H with soybean fiber (HS), or with AGIQ (HQ), or with both (HSQ). Quercetin derivatives in plasma, feces, urine, and cecal content were quantified by high-performance liquid chromatography to assess the bioavailability of quercet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“… 7 Among them, quercetin, genistein, and citrus flavonoids, such as hesperidin and eriocitrin, have been studied. 8–13 …”
Section: Introductionmentioning
confidence: 99%
“… 7 Among them, quercetin, genistein, and citrus flavonoids, such as hesperidin and eriocitrin, have been studied. 8–13 …”
Section: Introductionmentioning
confidence: 99%
“…Kun Dai et al demonstrated that chlorogenic acid in peaches has significant antioxidant and hypoglycemic effects, which could inhibit α-glucosidase, α-amylase and scavenges free radical [ 14 ]. Aphichat et al discovered that quercetin could improve glucose metabolism and glucose tolerance [ 15 ]. Yin et al revealed that ellagic acid-rich oak extracts notably reduced serum MDA and SOD and inhibited α-glucosidase and α-amylase activities in diabetic mice [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study in rats fed a high-fat high-sucrose diet has shown that the combination of a glycosylated quercetin derivative and soyabean fiber prevented dietary glucose intolerance and was accompanied by an increase in plasma GLP-1 levels. In addition, GLP-1 levels were positively correlated with quercetin concentrations in plasma, thereby demonstrating the effect of soybean fiber and quercetin on reducing the risk of glucose intolerance and imbedding diabetes [ 45 ].…”
Section: Bioactivitymentioning
confidence: 99%
“…Quercetin can be a powerful antioxidant by creating complexes after taking into account its chemical properties related to its high solubility and bioavailability [ 42 , 43 , 44 ]. Its action against diabetes is explained by its effect on hepatic HepG2 cells, where it alleviates oxidative stress due to hyperglycemia, and activation of the Nrf2 metabolic pathway in pancreatic tissue [ 45 , 46 ]. Moreover, in the clinical field, Rauf et al [ 47 ] stressed that quercetin is both an inhibitory and a preventive agent for cancer, and can assist treatments against the disease, such as chemotherapy.…”
Section: Introductionmentioning
confidence: 99%